THE ANTIMICROBIAL ASSESSMENT OF SOME NIGERIAN HERBAL SOAP. - Igbeneghu, O. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Twenty samples of herbal soaps were evaluated for their antimicrobial activity against bacteria and yeast of significance in skin infections with the aim to provide some justification for the continued use of the soaps in the management of superficial skin infections. All the soaps were found to possess antimicrobial activity in a concentration and organism dependent manner. The soaps were more active against the gram positive organisms than the Gram negative organisms while none of the soaps had activity against the tested yeasts. Only 35% of the soaps were appropriately packaged with adequate directions for use and storage. The study showed that the tested soaps possessed antimicrobial properties and they can contribute to the treatment and management of skin infections caused by bacteria if well prepared with the appropriate plant materials to target specific causative organisms and packaged with appropriate directions for use and storage.